Handling Practices and Quality Attributes Along the Supply Chain of gboma (Solanum Macrocarpon): A Leafy Vegetable in Southern Benin - Fernande G. Honfo; Mênouwesso H. Hounhouigan; D. Sylvain Dabade; Mathias Hounsou; Barbara Gotz; Antonia Albrecht; Judith Kreyenschmidt; D. Joseph Hounhouigan (International Journal of Food Studies)
gboma is a leafy vegetable commonly consumed in Benin, which plays an important role in food security. This study assessed the handling and preservation practices as well as quality attributes of gboma along the supply chain in Southern Benin. A survey among 785 people (285 producers, 180 whole salers/retailers, and 326 consumers) living in four Departments of Benin was conducted to evaluate the consumption frequency, the transportation mode, the preservation methods and quality attributes of gboma during purchasing. The survey revealed that, in general, gboma sauce is consumed twice to three times a month in all the departments covered. Different practices, including humidification, were used to preserve the leaves during selling. Traditional baskets or old clothes were used for the transportation and storage of gboma. Important quality attributes mostly used by actors during purchasing were freshness and color followed by physical damage and, to a lesser extent, weight and leaf surface at different degrees. gboma is currently sold in informal markets; however, improving handling and selling practices could preserve the freshness of this leafy vegetable that could then be placed in conventional supermarkets. Thereby, the selling and consequently the production level will increase, with positive impact on the income of producers.